Optimisation of bidrectional impulse turbines for wve power generation - Banks, K (Cranfield University, 2009)
The generation of electricity from ocean waves using oscillating water column (OWC) wave energy converters is currently uneconomic due to the high capital cost and low efficiencies of such devices. The bidirectional air turbines utilised in OWCS are one of the principal sources of inefficiency and a significant increase in their performance would improve the prospects of commercial scale wave power generation. The ability of computational fluid dynamics (CFD) to predict the performance of both Wells and impulse type bidirectional turbines for use in OWCS was examined by comparison with experimental results taken from the literature. A design process was then undertaken for a datum impulse turbine and a novel high-efficiency impulse turbine arrangement. Numerical performance predictions are presented with a comparison against experimental data from a large-scale oscillating-flow test rig. An automated design and aerodynamic optimisation system was subsequently developed for application to this novel impulse turbine design. The optimiser employs a hybridised genetic algorithm along with Kriging meta¬models to significantly decrease the number of expensive calls to the 3D-CFD code used to evaluate the objective function. Comparisons to a number of state of the art optimisation algorithms from the literature on some mathematical test functions indicated that the optimiser had equivalent or better performance for most problems. A parameter study was carried out to investigate the effect of various turbine in design variables, before undertaking a 14-variable global design optimisation. A 5-variable optimisation exercise was then performed to investigate the effi- ciency gains that could be achieved by using three-dimensional rotor blades. Substantial gains in performance were attained and the predicted levels of efficiency are significantly higher than those previously reported in the literature for other bidirectional impulse turbine designs.